Polish and Norwegian Advertising Texts – Linguistic Analysis - Kabata, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The following research incorporated newspaper advertisements of the most popular grocery stores in Norway and Poland in the category of small chain stores and medium-sized stores. Focusing the study on the verbal message allowed for an in-depth analysis of linguistic aspects, as presented in detail in this article. The linguistic material was collected at the same time in both countries (from September 20 to December 31, 2021). The research methodology of the collected material included analysis of the linguistic structures and content of the advertising message, allowing for understanding the mechanisms of consumption and anticipated purchasing reactions. In addition, I observed trends in consumer preferences. Conclusions: basically, advertisements in newspapers for Norwegian and Polish customers are not radically different from each other. All judgements about the world as a global village from the point of view of the conducted analyses are justified. The circle of values for both contemporary societies is similarly exposed, and although the accents are distributed differently, it does not change the overall picture of the situation. The differences that appeared in the analyzed material come down to differently-placed accents on value.